Constructing Authoritative Answers to a Latent Crisis? Strategies of Puzzling, Powering and Framing in Dutch Climate Adaptation Practices Compared. Issue 1 (1st January 2016) - Van Buuren, Arwin; Vink, Martinus; Warner, Jeroen
Abstract: While adaptation tends to be approached as an issue for policy analysis, framing and powering strongly interact with policy analysis (puzzling) and are at least as important for adequate outcomes in such an ambiguous context. The present contribution compares and analyzes two Dutch adaptation strategies in the Central Netherlands: (1) realizing a flood bypass channel near the town of Kampen and (2) exploring possibilities to raise the water level of Lake IJssel, enhancing the country's freshwater storage capacity. The article concludes that in both trajectories there is an important role for policy analysis (puzzling) but the cases differ strongly in the way actors frame the intervention, their corresponding powering strategies and the policy outcomes.